Dual-Process Bereavement Group Intervention (DPBGI) for Widowed Older Adults. (17th August 2018) - Chow, Amy Y M; Caserta, Michael; Lund, Dale; Suen, Margaret H P; Xiu, Daiming; Chan, Iris K N; Chu, Kurtee S M
Abstract: Background and Objectives: To examine the primary and secondary outcomes of a theory-driven group bereavement intervention for widowed older adults through a cluster-randomized controlled trial. Research Designs and Methods: Twelve community centers providing health and social services for elderly people were randomly assigned to the experimental condition, the dual-process bereavement group intervention-Chinese (DPBGI-C) and to the control condition, the loss-oriented bereavement group intervention-Chinese (LOBGI-C). Both interventions comprised weekly, 2-hr sessions for 7 weeks followed by a 4-hr outing in the eighth week. Of 215 widowed older adults contacted and assessed, 125 eligible participants were interviewed three times—preintervention, postintervention, and at a 16-week follow-up—to assess complicated grief symptoms, anxiety, depression, loneliness, and social support. Results: Using intention-to-treat analysis, both interventions produced improvements in grief, depression, and social support, but effect sizes were larger with the DPBGI-C. The participants in the DPBGI-C condition also reported reduced anxiety, emotional loneliness, and social loneliness, whereas those in the LOBGI-C condition did not. There were interactions between intervention type and time with respect to grief, anxiety, emotional loneliness, and social loneliness. Discussion and Implications: Although traditional LOBGI-C can help to reduce grief and depression in bereaved older adults, the DPBGI-C was found to be superior as it had a greater and more extensive impact on outcomes. This is the first study of the effectiveness of this evidence-based, theory-driven intervention for widowed Chinese older adults and has implications for theory building and practice.